Team USA injury and illness incidence at the 2022 Beijing Winter Olympic and Paralympic Games - Anderson, T.; Cali, M. G.; Clark, S. C.; Hasley, I.; Larson, E. G.; Noble-Taylor, K. E.; Robinson, D. M.; Post, E.; Finnoff, J. T.; Adams, W. M. (British Journal of Sports Medicine, 2024)
Objective The purpose of this study was to determine the injury and illness incidence from Team USA athletes from the 2022 Beijing Winter Olympic and Paralympic Games and assess any sex-based differences or differences between Olympic and Paralympic athletes.